Evaluation of EGFR as a prognostic and diagnostic marker for head and neck squamous cell carcinoma patients - Polanska, Hana; Raudenska, Martina; Hudcová, Kristyna; Gumulec, Jaromir; Svobodova, Marketa; Heger, Zbynek; Fojtu, Michaela; Binkova, Hana; Horakova, Zuzana; Kostrica, Rom; Adam, Vojtech; Kizek, Rene; et al. (Oncology letters, 2016)
Approximately 90% of all head and neck tumors are squamous cell carcinomas. The overall survival of patients with head and neck squamous cell carcinoma (HNSCC) is low (≤50%). A non-invasive marker of disease progression is sorely required. The present study focused on the plasmatic levels of epidermal growth factor receptor (EGFR) in HNSCC patients (N=92) compared with healthy (N=29) and diabetic [type 2 diabetes mellitus (T2DM); N=26] controls. Enzyme-linked immunosorbent assay using antibodies against the extracellular region of EGFR (L25-S645) was performed. No significant changes were observed between diabetic and healthy controls. However, there were significantly higher EGFR plasma levels in HNSCC patients compared with both control groups (P=0.001 and 0.005, respectively). Receiver operating characteristic curve analysis identified a sensitivity of 76.09%, a specificity of 67.27% and an area under curve of 0.727 for this comparison. No significant association was observed between EGFR plasma levels and tumor stage, tumor grade, lymph node or distant metastasis occurrence, smoking habit or hypertension. However, the presence of human papillomavirus infection and T2DM in HNSCC patients had borderline effect on the plasma EGFR levels. Survival analysis revealed no significant influence of plasmatic EGFR levels on the overall and disease-specific survival of HNSCC patients. In conclusion, EGFR plasma levels appear to be a relatively promising diagnostic, but poor prognostic, HNSCC marker.
Keywords: EGFR; head and neck tumors; biomarker; plasma; diagnosis; spinocellular cancer